2008
DOI: 10.1103/physreve.78.011306
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche dynamics on a rough inclined plane

Abstract: Avalanche behavior of gravitationally-forced granular layers on a rough inclined plane are investigated experimentally for different materials and for a variety of grain shapes ranging from spherical beads to highly anisotropic particles with dendritic shape. We measure the front velocity, area and the height of many avalanches and correlate the motion with the area and height. We also measure the avalanche profiles for several example cases. As the shape irregularity of the grains is increased, there is a dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 51 publications
(89 reference statements)
7
67
0
Order By: Relevance
“…Moreover, aspherical particles demonstrate increased ordering near the walls (an effect which is more pronounced for the smooth walls). 33,34 The smooth wall experiments, however, show that when normalized by the size and shape dependent random loose packing fraction, / l , the relative apparent viscosity shows no dependence on the particle size or shape. Comparing the nylon to SAN particles, both have a high sphericity (w ¼ 1.00 and 0.98), but the nylon particles …”
Section: -7mentioning
confidence: 99%
“…Moreover, aspherical particles demonstrate increased ordering near the walls (an effect which is more pronounced for the smooth walls). 33,34 The smooth wall experiments, however, show that when normalized by the size and shape dependent random loose packing fraction, / l , the relative apparent viscosity shows no dependence on the particle size or shape. Comparing the nylon to SAN particles, both have a high sphericity (w ¼ 1.00 and 0.98), but the nylon particles …”
Section: -7mentioning
confidence: 99%
“…With l/b ave = 1.17, the Cataphote grains show a slightly greater average asphericity than the large Mo-Sci grains, l/b ave = 1.12. It has been demonstrated that higher asphericity leads to a larger angle of repose 14 . Another reason for the discrepancy could be that the two larger types of grain also produce different packing densities, φ, whish would be a natural consequence of their aspherity 32 .…”
Section: A Angle Of Repose Measurementsmentioning
confidence: 99%
“…It has been shown experimentally that friction can also play an important role in granular segregation 9,10 , for example in the sharp transition from the reverse brazil-nut effect to the brazilnut effect 10 , but other work shows that this is not always the case 11 . The dynamical properties of avalanches were shown to depend on inter-particle friction, and two friction-dependent scenarios for granular avalanches on an incline were identified [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…[25] by simulation and in Ref. [16] by experiment. It was found that spherical grains have a lower angle of repose than nonspherical grains and that for nonspherical grains the angle of repose fluctuates much stronger.…”
Section: Critical Anglesmentioning
confidence: 99%
“…Moreover it was shown that long thin rods are able to jam into a solidlike state [13], which can strongly influence the avalanche behavior in such systems. Front velocity, area, and height of avalanches on a rough inclined plane have been already investigated experimentally for different grain shapes [16].…”
Section: Introductionmentioning
confidence: 99%